Does dual citizenship increase naturalization? Evidence from Indian immigrants in the US - Daniel Naujoks (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2012)
This paper shows that the availability of dual citizenship, or here Overseas Citizenship of India (OCI), leads to higher naturalization rates in the country of residence. The analysis is based on three distinct naturalization rates, calculated on the basis of annual immigration flows and naturalizations seven years later; the resident population eligible for naturalization; and naturalization records for specific immigrant cohorts. To isolate effects specific to India as the country of origin from general factors in the U.S., the development of naturalization rates for Indian, or India-born, immigrants is juxtaposed with the respective rates for all Asian immigrants to the U.S. and for all immigrants to the U.S. as comparison groups. Contextualizing the naturalization decision, considering factors in the country of origin, destination, as well as in the migrant community alike, the paper finds that, depending on the metric used, the naturalization rate of Indian immigrants grew stronger than that of the chosen comparison groups by 2 to 12.8 percentage points.
Keywords: 330; dual citizenship; naturalization; nationality; migration; emigrant citizenship; overseas citizenship of India; diaspora; political incorporation; Staatsangehörigkeit; Einwanderungsrecht; Inder; USA